Religiöse Neutralität und Rundfunkfreiheit: Drittsendungsrechte für Religionsgemeinschaften - Trapp, Dan Bastian (Jus Ecclesiasticum, 2013)
Public and private broadcasting services are bound by law to give certain religious groups adequate broadcasting time if they wish. Dan Bastian Trapp studies the constitutional requirements necessary in order for the state, which is bound to neutrality in religious and ideological matters, to give churches and other religious groups these special rights of access.